Antibacterial Activity of Extract A. luteocarpa - Tita Juwitaningsih; Destria Roza; Nora Susanti (Universitas Negeri Medan, 2018)
Meat is one of the food products that can easily be damaged, ( therefore it is necessary to preserve the process). therefore it needs to be done the process of preservation. In this study we studied the anti-bacterial activity of Alpinia luteocarpa extract against fresh meat rot bacteria, with paper disc diffusion method which is the standard recommended by the Clinical and Laboratory Standard Institute (CLSI,2012). The results of antibacterial activity test showed extract and fraction of A. luteocarpa able to inhibit bacterial growth B.cereus ATCC 21772 and. K. pneumonia ATTC 13773. The bacteriostatic properties of the extract and fraction of A. luteocarpa against B. cereus ATCC 21772 and K. pneumonia ATTC 13773 were better than the positive control of chlorhexidine antibiotics (500 μg / mL) with inhibition zones 9-11 mm and 7-9 mm.